Larvicidal and ovicidal activities of Artocarpus blancoi extracts against Aedes aegypti - Maria Ruth B. Pineda-Cortel; Rachel Joy R. Cabantog; Paulo M. Caasi; Charles Anson D. Ching; Joseph Benjamin S. Perez; Paulo Gabriel M. Godisan; Cheska Marie G. Latorre; Danielle R. Lucero; Reginald B. Salonga (Taylor & Francis Group, 2019)
Context: Dengue control may be done by targeting its vector. In this study, we used Artocarpus blancoi (Elm.) Merr. (Moraceae) leaves, an endemic hematophagous insect repellent as a larvicide and ovicide. Objective: We investigated the larvicidal and ovicidal activities of its soluble crude ethanol extract and the hexane, aqueous, and ethyl acetate fractions against Aedes aegypti. Materials and methods: Third to early fourth instar A. aegypti larvae were exposed to 200, 400, 600, 800 and 1000 ppm of crude ethanol; to 10, 20, 40, 60 and 80 ppm of ethyl acetate; and to 500, 750, 1000, 1250 and 1500 ppm of hexane fractions of A. blancoi; 48 h LC50 and LC90 values were determined. For the ovicidal assay, an average of 25 eggs/paper strip was used; inhibition of egg hatchability was counted 72 h after exposure. Fractions were screened qualitatively for phytochemicals. Results: Ethyl acetate soluble fraction gave the lowest LC50 value (18.59 ppm) followed by the crude ethanol (411 ppm), hexane (685 ppm) and aqueous (20,158 ppm) fractions. Similarly, ethyl acetate soluble fraction appeared to be the most ovicidal (80 ppm). Larvicidal and ovicidal activities of the fractions were dose dependent. Qualitative phytochemical screening revealed moderate presence of glycosides and sterols and trace amounts of triterpenes, flavonoids, saponins and tannins. Discussion and conclusions: A. blancoi is a potential larvicide and ovicide against A. aegypti, and future studies isolating the specific components responsible for such actions would be significant.